Implementation of Trenggalek Regent Regulation Number 01 of 2019 Concerning Implementation Guidelines Cool Musrena in Support Development Planning Meeting - Susanto, Joko; Andriyanto, Andriyanto (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2023)
Women's participation in development planning and budgeting in the Development Planning Meeting (Musrenbang) is still a challenge today. In response to this, the Trenggalek Regency Government has issued a policy in the form of Regent Regulation Number 01 of 2019 which is a guideline for holding deliberations for women, children, disabilities and other vulnerable families. Or abbreviated Musrena Keren. This public policy publication provides an opportunity for the full participation of vulnerable women and families in gender mainstreaming (PUG) and gender responsive budgeting (ARG) from the lowest level, namely at the village level. This study aims to comprehensively detail the innovations of the Keren Musrena in Trenggalek Regency. By using a qualitative approach, data for this study were collected from focus group discussions (FGD), in-depth interviews and desk reviews (documentary/documentary reviews). The results of this study are: 1. Increasing the motivation and awareness of women at the village and district levels in participating in gender responsive budgeting and development planning. 2. Musrena Keren is based on the principles of equality, gender fair budgeting, dialogue, against domination, pro-vulnerable groups, non-discrimination and inclusive development Increasing the motivation and awareness of women at the village and district levels in participating in gender responsive budgeting and development planning. 2. Musrena Keren is based on the principles of equality, gender fair budgeting, dialogue, against domination, pro-vulnerable groups, non-discrimination and inclusive development Increasing the motivation and awareness of women at the village and district levels in participating in gender responsive budgeting and development planning. 2. Musrena Keren is based on the principles of equality, gender fair budgeting, dialogue, against domination, pro-vulnerable groups, non-discrimination and inclusive development.